Microplastic sink that cannot be ignored in chemosynthetic organisms. (April 2023) - Zhang, Kangning; Liang, Junhua; Sha, Zhongli; Zhou, Li; Zheng, Shan; Sun, Xiaoxia
Abstract: Marine microplastic (MP) pollution is a widespread concern; however, to date, MP pollution in chemoautotrophic ecosystems remains largely unknown. This study focuses on the cold seep in the South China Sea. Two dominant species, namely mussel ( Gigantidas platifrons ) and squat lobster ( Shinkaia crosnieri ), were collected for examining the MP pollution. MPs were present in both mussels and squat lobsters with abundances of 0.13 ± 0.04 and 0.17 ± 0.06 items/ind., respectively. MPs were mainly fibrous (62.5 %) and transparent (45.8 %). The main polymer type was polyester (54.2 %). About 86.5 MPs/m 2 were found inhabiting mussels and squat lobsters—a value comparable to those reported in benthos. This pilot report on MP pollution in cold-seep species provides key information for studies on MP pollution in chemoautotrophic ecosystems and evidence regarding a potential biological MP sink. The role of cold-seep organisms in MP retention and transport in the regional sea merits further attention. Highlights: Microplastic pollution was found in a chemoautotrophic ecosystem. Microplastics in cold-seep species were revealed. Microplastic abundance in cold-seep species was 0.13–0.17 items/individual. Cold-seep organisms may play an important role in microplastic transport.